Effect of Calcination Temperature on the Photocatalytic Activity of Zn2Ti3O8 Materials for Phenol Photodegradation - Krisfian Tata Aneka Priyangga; Yehezkiel Steven Kurniawan; Leny Yuliati (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Zinc titanate (Zn2Ti3O8) is a bimetal oxide material that is especially attractive as a photocatalyst. In the preparation of the Zn2Ti3O8, the calcination temperature is a crucial parameter. Hence, in the present work, we aimed to synthesize the Zn2Ti3O8 materials from zinc(II) nitrate and titanium(IV) isopropoxide as precursors by using a sol-gel method and followed by calcination at 700, 900, and 1100 °C to give ZT-700, ZT-900, and ZT-100 materials, respectively. The ZT materials were characterized using Fourier transform infrared (FTIR), diffuse reflectance ultraviolet-visible (DR UV-vis), and fluorescence spectroscopies. It was confirmed that the ZT materials contained O−Ti−O, Zn−O−Ti, Zn−O, Ti−O−Ti, and Ti−O functional groups as shown from their FTIR spectra. Similar fluorescence properties were only observed on the ZT-700 and ZT-900. From the bandgap energy analysis, ZT-700 and ZT-900 contained spinel and cubic Zn2Ti3O8 (spl-Zn2Ti3O8 and c-Zn2Ti3O8) crystal phases), while ZT-1100 contained c-Zn2TiO4 and TiO2 rutile crystal phases. The kinetic analysis of photocatalytic phenol degradation showed that both ZT-700 and ZT-900 materials exhibited high photocatalytic activity with the reaction rate constants of 0.0353 and 0.0355 h−1, respectively. These values were higher than that of the ZT-1100 (0.0206 h−1). This study demonstrated that calcination at 700 and 900 °C resulted in the formation of the spl-Zn2Ti3O8 and c-Zn2Ti3O8 phases, which were effective as the photocatalyst, but the formation of c-Zn2TiO4 and rutile TiO2 at calcination of 1100 °C deteriorated the photocatalytic activity. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).